Identification and abundance of plankton as an indicator of the presence of mahseer fish (Tor sp.) in the Leuser River Lokop Area, East Aceh, Aceh - Risdian Syahputra; Suri Purnama Febri; Teuku Fadlon Haser; Andri Yusman Persada; Suraiya Nazlia (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
The abundance of plankton can describe aquatic life. The Jurung fish is a plankton feeder freshwater fish which has high economic value. This study aimed to identify plankton recognition as an indicator of the presence of Jurung fish (Tor sp.) in the Leuser area of the Lokop River in Aceh and analyze the physico-chemical factors associated with attracting plankton in the Lokop River. This research was conducted from February to March 2021. The research showed that the number of types of plankton found in the Lokop river was 17 types (13 phytoplankton and 4 zooplankton). Diversity index value of 1.538364 – 2.133691 and evennes index of 0.542975 - 0.753099 were classified as mesotropic waters with moderate fertility levels. In general, based on observations of plankton in the Lokop river, Jurung fish could be cultivated from upstream to downstream. However, it is better to be at station 1 (upstream) because there are still a lot of plankton species so that the food needs of the Jurung fish can be fulfilled.